IS WELFARE THE CORRELATION UNITY OR THE STRUGGLE OF ITS COMPONENTS? (Based on the data of the countries of the former soviet union) - O. V. Pogharnitskaya; E. G. Matyugina; G. Y. Boyarko; A. A. Mitsel; E.V. Vaganova (Scientific Journal of Pedagogy and Economics, 2019)
The article is to present such welfare components as human development index, economic growth, energy consumption, ecological condition. The object of the research is the dynamics of the welfare of countries from the former Soviet Union. For evaluation a set of such criteria as gross domestic product per capita, human development index and energy consumption per capita have been used. In addition such indicators as gross domestic product per unit of energy use; emissions of СО2, methane and greenhouse gases per capita, and area of forests have also been investigated. Factual data for the period 1997-2015 have been used. The research is related to the common stages of the transformation and parameters of the development of countries from the former Soviet Union over a certain period of time. Nevertheless, countries that have a common past have demonstrated a significant variation in the dependencies of the studied indicators. Based on the results of the correlation analysis, a group of countries showing a high dependence on all the welfare criteria on the factors considered (Russia, Armenia, Azerbaijan, Belarus) has been chosen. A positive correlation of human development index has been found in codependency of human development index and gross domestic product per unit of energy use. A positive correlation of gross domestic product per capita indicator has been found in codependency of gross domestic product per capita and gross domestic product per unit of energy use; gross domestic product per capita and CH4 per capita (exception Ukraine). A study of dependencies allows us to equate economic growth and welfare. It is common for the countries from the former Soviet Union (correlation coefficient for most countries is 0.95) between economic growth rates and energy consumption, as well as energy consumption and CO2 emissions (correlation coefficient 0.85–0.997). All countries show an obvious dependence of economic growth on energy consumed. A slightly weaker correlation has been noticed in Kyrgyzstan and Kazakhstan. A negative correlation between energy consumption per person and gross domestic product per unit of energy use has been found in Uzbekistan. The reason is the growth of the population in spite of the decrease in energy consumption. A negative correlation between the gross domestic product per capita and the forest area is common for Kazakhstan, Kyrgyzstan and Tajikistan, which have a small forest fund. The data obtained allowed us to classify countries according to the level of energy consumption and dependence on the sources of natural resources. Energy consumption as a welfare criterion has its own specific number of dependencies. It is this criterion that has the maximum number of dependencies with a strong negative correlation for countries from the former Soviet Union. That lays the groundwork for expanding the list of correlating factors in future research.